2001
DOI: 10.1007/s00335-001-3039-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerd4, third member of the d4 gene family: expression and organization of genomic locus

Abstract: Two members of the d4 family of presumptive transcription modulators, neuro-d4 (Neud4) and ubi-d4/Requiem (Req), have been characterized previously. We cloned and characterized the third member of this gene family, cer-d4 (Cerd4), from chicken and mouse cDNA libraries. The expression patterns of Cerd4 gene in both species are similar and more restricted than expression patterns of other two d4 genes. The main sites of Cerd4 expression are retina and cerebellum, where multiple transcripts could be detected. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Three subtypes (DPF1, DPF2, and DPF3) have been identified, and they are evolutionarily conserved from nematodes to human. DPF2 is widely expressed (30), whereas DPF1 expression is restricted to neuronal systems, and DPF3 is restricted to retina and cerebellum (31,32).…”
Section: Purification and Identification Of Err␣-associated Proteins-mentioning
confidence: 99%
“…Three subtypes (DPF1, DPF2, and DPF3) have been identified, and they are evolutionarily conserved from nematodes to human. DPF2 is widely expressed (30), whereas DPF1 expression is restricted to neuronal systems, and DPF3 is restricted to retina and cerebellum (31,32).…”
Section: Purification and Identification Of Err␣-associated Proteins-mentioning
confidence: 99%
“…Importantly, transactivation mediated through RelA/p50 (Fig. 1C, lanes 14 -18 compared with lane 13), RelB/p52 (lanes 20 -24 compared with lane 19), and c-Rel/p50 (lanes 8 -12 compared with lane 7) was enhanced by the endogenous expression of any of the five candidate proteins (lanes [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. No significant differences were found among these five proteins in terms of the enhancement of any of the three NF-B dimers, suggesting that all potentially function as co-activators of NF-B in any context, at least when expressed at high levels.…”
Section: High Expression Of Each Member Of the D4 Family And Phf10mentioning
confidence: 99%
“…We also found that semen progressive motility (Grade a + b) was greatly reduced in CT heterozygotes ( P = 0.0003) and the concentration of semen in CT heterozygotes was also low ( P = 0.0319). DPF3 encodes a member of the D4 protein family of zinc finger proteins which is implicated as an epigenetic factor specifically binding acetylated and methylated lysine residues of histone 3 and histone 4 to provide easy access of transcription factors to DNA 1516…”
Section: Discussionmentioning
confidence: 99%